2020
DOI: 10.1155/2020/7656031
|View full text |Cite
|
Sign up to set email alerts
|

High JAK2 Protein Expression Predicts a Poor Prognosis in Patients with Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Background. Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal malignancies worldwide. The JAK/STAT signaling pathway is involved in pancreatic cancer tumorigenesis. However, the prognostic value of JAK2 expression in resectable PDAC is unclear. Method. In this study, we performed a clinicopathological analysis of 62 resectable PDAC cases with a primary focus on survival. JAK2 expression was examined by immunohistochemistry. The relationship between JAK2 expression and clinicopathological feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…To explore the underlying pro-apoptosis mechanism of panaxadiol, we performed molecular docking and western blot. According to the literature, blockage of JAK2-STAT3 signaling pathway was associated with apoptosis of pancreatic cancer [ 14 , 15 ], and the high expression of JAK2 in pancreatic cancer patients predicts an unfavorable prognosis in most cases [ 16 ]. In molecular docking analysis ( Figure 5A and 5B ), panaxadiol shows promising affinity with STAT3 and the lowest binding energy which means the best binding affinity with the target site was −5.7 (kcal/mol) among them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the underlying pro-apoptosis mechanism of panaxadiol, we performed molecular docking and western blot. According to the literature, blockage of JAK2-STAT3 signaling pathway was associated with apoptosis of pancreatic cancer [ 14 , 15 ], and the high expression of JAK2 in pancreatic cancer patients predicts an unfavorable prognosis in most cases [ 16 ]. In molecular docking analysis ( Figure 5A and 5B ), panaxadiol shows promising affinity with STAT3 and the lowest binding energy which means the best binding affinity with the target site was −5.7 (kcal/mol) among them.…”
Section: Resultsmentioning
confidence: 99%
“…In previous researches, JAK2-STAT3 signal pathway has been proved to play a critical role in tumorigenesis, proliferation, stroma modification, chemoresistance, immune cell infiltration, patient survival time in pancreatic cancer [ 16 , 29 , 30 ]. After receiving the stimulation of the upstream signal, JAK2 is activated by tyrosine phosphorylation of the receptor, and this also leads to phosphorylation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High JAK2 expression predicts a poor prognosis in patients with PDAC. 80 Several studies have shown that the JAK/STAT pathway is involved in inflammatory processes in pancreatic cancer. Both type 1 (i.e., IFNα and IFNβ) and type 2 (i.e., IFNγ) interferons can upregulate programmed cell death 1-ligand 1 (PD-L1) expression via the JAK-STAT signaling pathway in pancreatic cancer.…”
Section: Characteristics Of Pancreatic Cancermentioning
confidence: 99%
“…The Janus-associated kinase-signal transducer and activator of transcription (JAK-STAT) pathway is involved in the development of multiple human cancers [88]. Four JAK and seven STAT family members have been described in humans, although significant elevations in expression and activation of JAK1/2 and STAT3, in particular, have been observed in pancreatic cancer patients [89][90][91]. Overexpression of JAK-STAT pathway components, such as IL-6, EGFR, and Src, have also been seen in pancreatic cancer [87].…”
Section: Targeting Signaling Pathways 61 Jak/stat Pathwaymentioning
confidence: 99%